Effects of Fluoride Exposure During Pregnancy in Mice Brain Neurogenesis (Mus musculus) - Siti Sarahdeaz Fazzaura Putri; Irfannuddin Irfannuddin; Krisna Murti; Yudianita Kesuma; Hardi Darmawan; Noriyuki Koibuchi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Fluoride is a type of micromineral found in teeth and bones. This mineral is also found in nature, such as in soil, water, plants, rocks, and even air. Fluoride can cross the placental barrier and diffuse into the cord blood, with a range from 60% to 91% of maternal fluoride. Maternal fluoride exposure during pregnancy and lactation can affect learning ability, memory, and expression of glutamate receptors. This study aimed to determine the effect of fluoride exposure during pregnancy and lactation on brain neurogenesis in vivo. Methods: In vivo, experimental study using mice (Mus musculus) C57BL/6 as many as 60 brood mice (20 males and 40 females) and as many as 30 offspring mice. Mice broodstock were first mated to produce offspring. During pregnancy, the female mice were exposed to fluoride (NaF). Exposure of broodstock mice to NaF was divided into 0 mg/L, 50 mg/L, 100 mg/L, and 150 mg/L exposure groups. Expression of PSD-95 protein was carried out by immunohistochemical examination of mouse brain tissue. Data analysis was carried out with the help of SPSS using univariate and bivariate methods. Results: There was a decrease in the expression of PSD-95 with increasing exposure to NaF doses during pregnancy and lactation. Giving NaF at a dose of 50 mg/L did not decrease PSD-95 expression because the results were not different from the control. In contrast, the administration of NaF doses that can reduce the expression of PSD-95 are doses of 100 and 150 mg/L. Conclusion: Fluoride exposure during pregnancy contributed to a decrease in mice brain neurogenesis, as indicated by the expression of the PSD-95 protein in the hippocampus area.